(untitled) - Crapo, Richley H (Boston, 2003)
This text offers an alternative to the case-driven approach that the sole use of a reader tends to foster. It provides students with ways of conceptualizing what religion is, what its social and psychological functions are, the nature of religious symbolism and religious behavior, and the organizational structure of religions. This text covers all the standard topics (e.g., ideology and symbolism, ritual and ceremony, organizational forms, and social and psychological functions of religion) as well as ones of more recent interest such as religion and gender, the psychology of religion, and pilgrimage.
Keywords: Religion,Tôn giáo